Phenotypic effects of in vitro miR-141 expression modulation in bladder cancer - Lai, Jiun Yee (2013)
Cancer initiation and progression is a multi-step process that involves the accumulation of somatic mutations that lead to the dysregulation of specific genes. Epigenetic modifications play a key role in the regulation of gene expression during cellular differentiation. Amongst the emerging epigenetic players in cancer biology are miRNAs. MiRNAs are short non-coding endogenous RNAs that regulate gene expression by inhibiting translation efficiency or enhancing mRNA decay.Depending on the mRNA target it regulates, in cancer, miRNAs can act either as tumour suppressors or promoters. Hence, the orchestration of miRNA regulation and function is highly biological significant in cancer initiation and progression. In this study, we aimed to investigate the association of miR-141 expression and bladder cancer cell phenotypes. Using in silico prediction tools, several genes that were found to be dysregulated in bladder cancer were predicted to be potentially regulated by miR-141. ZEB family members, MAP2K4 and DLC1 genes were found to be potentially targeted by miR-141 and were associated with a malignant invasive potential. EJ28 invasive bladder cancer cell line was selected in this study due to its invasive phenotype. To characterise the phenotypic effects of miR-141 expression modulation, several phenotypic assays (cell cycle, migration and matrigel invasion) were conducted after the ectopic upregulation of miR-141 expression in vitro by miR-141 mimics in EJ28 cells. All the experiments were completed in three independent replicates (n=3). The over expression of miR-141 was confirmed in miR-141 upregulated EJ28 cells by RT-qPCR quantification. MiR-141-over expressing cells demonstrated no apparent differences in cell-cycle distribution as compared to untransfected and mock controls. Therefore upregulation of miR-141 does not affect the cell cycle.Using the cell migration assay, miR-141-over expressing cells exhibited adecrease in the relative gap closure rate as compared to untransfected and mock controls.Specifically, aminor shift in relative gap closure rate was observed between9 and24 hours after wounding.The number of invaded cells using the matrigel invasion assay was significantly lower inmiR-141-over expressing cells as compared to both untransfected and mock control groups of cells(T-test, p<0.05, n=3). Thus, miR-141 expression impacts the invasive potential of EJ28 cells. In conclusion, the over expression of miR-141 decreased the migratory and invasive potential of EJ28 cells but did not affect the cell cycle. Although further validation is required, this study demonstrated miR-141 as a potential key regulator of bladder tumour igenesis and its utility as a potential prognostic and/ortherapeutic biomarker in bladder cancer management.